Measuring international capital mobility: A critical assessment of the use of saving and investment correlations - Stefan Sinn (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1991)
Economists have been interested in the degree of international capital mobility for a variety of reasons. E.g., the extent to which public deficits crowd out domestic investments depends on the ease with which domestic firms may access the international capital market. The welfare reduction due to a temporary negative shock to an economy (earthquake) is much less pronounced if it can borrow resources from abroad in order to tide itself over the initial period of reconstruction.
Keywords: 330; Kapitalmobilität; Sparen; Investition; OECD-Staaten